Analysis of Serum Glutamate Pyruvate Transaminase (SGPT) and Serum Glutamate Oxaloacetate Transaminase (SGOT) Levels in the Blood of Rat Offspring (Rattus norvegicus) Treated with Soybean (Glycine max L.) Extract and Zinc - Hafidz, Muhammad Al Hafidz; Busman, Hendri; Kanedi, M. Kanedi; Widiastuti, Endang Linirin (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2026)
Background: The liver is the largest metabolic organ and plays an important role in the body. Nutritional fulfilment is one factor in maintaining liver health. Liver function can be evaluated by measuring the levels of SGPT and SGOT enzymes in the blood. Soybean juice and zinc can support liver health by keeping SGPT and SGOT enzyme levels normal. Methods: This study was conducted between October and December 2024 at the Zoology Laboratory of the University of Lampung. This study used a Completely Randomized Design (CRD) included four treatment groups. Each treatment included five mice: control (K), treatment 1 (P1)- induced Soybean juice 0,6 mL/kg body weight (P2) induced Soybean 0,3 mL/kg body weight and Zinc 0,3 mL/kg body weight, and (P3) induced Soybean 0,6 mL/kg body weight and Zinc 0,6 mL/kg body weight for 14 days. Normal and homogeneous data were analyzed using analysis of variance (ANOVA) to determine whether the treatment's effect was significant. Differences were considered statistically significant at p < 0.05. Duncan's multiple interval post hoc test (=5%) was used to identify the most effective treatment. Result: Based on the results of the one-way ANOVA test with a 95% confidence interval, the average SGPT and SGOT levels in the K, P1, P2, and P3 treatments differ significantly. The average SGPT levels above show that the P2 and P3 groups experienced a significant decrease compared to the K and P1 treatments. Conclusion: Analysis of variance (ANOVA) showed that administering soya juice and zinc at an optimum dose of 1.2 mL/kg body weight can affect and maintain normal SGPT and SGOT levels.